REGULARITIES OF SPATIAL-TEMPORAL DISTRIBUTION AND EVALUATION OF ATMOSPHERIC PRECIPITATION OF SYUNIK MARZ (Proceedings of the YSU C: Geological and Geographical Sciences, 2013)
Taking into account the role and significance of precipitation in conditions of our low water-level country, water accumulation and usage during high waterlevel season, for productive usage of water resources and planning, was the aim to study and evaluate the regime of atmospheric precipitation and spatial-temporal regularities in Syunik Marz. To solve this task the results of observations of precipitation of Syunik Marz (1913–2010) were collected, worked out and analysed, were analysed the features of spatial-temporal distribution of precipitation of the region.
Keywords: regime of atmospheric precipitation; spatial-temporal distribution of precipitation; ratio between altitude and precipitation